Percutaneous transarterial balloon dilatation of the mitral valve: five year experience. Issue 2 (February 1992) - Babic, U U; Grujicic, S; Popovic, Z; Djurisic, Z; Pejcic, P; Vucinic, M
Abstract : OBJECTIVE–To examine the value of transarterial balloon dilatation of the mitral valve for treatment of patients with mitral stenosis over a period of five years. DESIGN–Analysis of patients' functional state, and haemodynamic and echocardiographic variables, before and immediately after the procedure and during a follow up of up to five years. SETTING–A cardiovascular centre in Belgrade, Yugoslavia. PATIENTS–Two hundred and ninety four patients who underwent percutaneous transarterial dilatation of the mitral valve between February 1985 and February 1990. RESULTS–Mean mitral valve area was enlarged by 109%. Complications included death (0.7%), severe mitral insufficiency (2.3%), mild mitral insufficiency (9.9%), cerebral embolism (2%), and injury to the femoral artery (2%). Two more patients died at two and 11 months after the procedure. Late cardiac surgery was needed in eight patients (mitral insufficiency in three, restenosis in three, thrombus in one, and endocarditis in one. Restenosis occurred in seven patients. Four of these underwent repeat dilatation and three had surgery. Improvement of symptoms was seen in 94% of patients during the follow up. CONCLUSION–Transarterial balloon dilatation of the mitral valve gave good results with acceptable morbidity and mortality and had some advantages over the anterograde approach.